The Use of Diopatra claparedii Grube, 1878 (Onuphidae, Polychaeta) as a Bioindicator of Heavy Metal Contaminations in the Donan Creek, Cilacap, Central Java, Indonesia - Sri Lestari; Windriarini Lestari; Eko Setio Wibowo; Phuping Sucharitakul; Joko Pamungkas (Marine Science Department Diponegoro University, 2025)
The Donan Creek is a coastal ecosystem in Central Java that is strongly affected by industrial activities. This study represents the first attempt to use the polychaete worms Diopatra claparedii Grube, 1878 (Onuphidae) as a bioindicator of heavy metal contaminations. The work was conducted between July and September 2023 at four sampling sites, designated from the farthest to the closest to the Indian Ocean. Samples of D. claparedii, sediment and water were collected at each site during low tide. The samples were analyzed for Cd, Cr and Pb concentration using Atomic Absorption Spectrophotometry. In addition, several other environmental parameters were also measured to examine the water quality of the creek. Our study highlights the capability of D. claparedii to accumulate all the three heavy metals. The concentrations of Cd, Cr and Pb in the body tissues of the worms ranged from 29.743 ± 0.011 mg.kg-1 to 50.036 ± 0.028 mg.kg-1, from 21.718 ± 0.024 mg.kg-1 to 40.032 ± 0.052 mg.kg-1, and from 20.068 ± 0.008 mg.kg-1 to 44.030 ± 0.000 mg.kg-1, respectively. These amounts were so far the highest among all other aquatic animals (i.e. bivalves, crustaceans and fishes) used as bioindicators in the Donan Creek. The heavy metal concentrations in D. claparedii were significantly correlated with those in the sediment (p < 0.05). In general, the levels of the metals were considerably higher in the more industrial area than those of the less industrial area (P<0.05). We further found that the concentrations of Cd, Cr and Pb as well as several other environmental parameters including BOD, COD, the total nitrate and phosphate in the water column of the creek did not meet the water quality standards stipulated by the Indonesian Government. These findings indicate that the ecosystem has been polluted by both heavy metals and organic matters. While environmental remediation is urgently required, a comprehensive review and improvement of industrial and domestic waste management practices in the region are equally essential to prevent further degradation.